Analisis Manajemen Keuangan Syariah Pada Koperasi Keluarga Kesehatan Syariah Jambi Tahun 2019-2021 - Nur Aisyah; Maulana Yusuf; Puteri Anggi Lubis (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
In 2019 there was a delay in paying mandatory deposits and sharia credit which affected the cooperative's financial management system. Financial management to measure the achievement of cooperative operations. Financial profitability from 2019-2021 has not been stable and to increase cooperative efficiency. Settlement of bad loans in the context of developing the national economy must run effectively and efficiently based on the principle of a simple, fast and low-cost trial. Settlement of bad credit is carried out by executing the collateral object in accordance with the mechanism specified in the provisions of the laws and regulations governing the collateral institution. The purpose of this study is to determine the factors that cause bad credit and to determine the effect on capital and accumulated profit losses of cooperatives. The method used in this research is a qualitative descriptive method, the steps include analysis of potentials and problems by means of a preliminary study through literature study and data collection through observation, interviews and documentation. The results of the study show that capital has no effect, then accumulated profit and loss only affects it because the performance and profits that are managed by cooperatives decrease, the profits received will also decrease. Then in completing the solution to the bad credit on several external and internal factors that occur, for solutions that are postponed installments and rescheduling are rescheduled with the total number of installments remaining the same according to the contract and obligations, then if someone's character is found to be difficult or in a difficult economic condition, the book will be deleted. This sharia cooperative has reserves for allowance for productive losses. As for suggestions, it is necessary to make a more detailed and measurable work plan containing strategies for achieving targets and controlling them periodically, taking into account the current situation and conditions.